2019
DOI: 10.1016/j.exer.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress induces ferroptotic cell death in retinal pigment epithelial cells

Abstract: The dysfunction and cell death of retinal pigment epithelial (RPE) cells are hallmarks of late-stage dry (atrophic) age-related macular degeneration (AMD), for which no effective therapy has yet been developed. Previous studies have indicated that iron accumulation is a source of excess free radical production in RPE, and age-dependent iron accumulation in RPE is accelerated in patients with dry AMD. Although the pathogenic role of oxidative stress in RPE in the development of dry AMD is widely accepted, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(95 citation statements)
references
References 53 publications
8
86
0
1
Order By: Relevance
“…Cells were maintained in DMEM, consisting of 10% FBS, 100 U/mL penicillin, and 100 U/mL streptomycin. They were maintained in a humidified environment with An association between ferroptosis and redox perturbations has been described previously (17,32); it is conceivable that ferroptosis may be modulated by MIOX overexpression in cisplatininduced tubular injury, since oxygen radicals are generated in the MIOX-initiated glucuronate/xylulose pathway (19). MIOX, a proximal tubular-specific enzyme, exacerbates kidney redox injury in multiple pathological states (33).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were maintained in DMEM, consisting of 10% FBS, 100 U/mL penicillin, and 100 U/mL streptomycin. They were maintained in a humidified environment with An association between ferroptosis and redox perturbations has been described previously (17,32); it is conceivable that ferroptosis may be modulated by MIOX overexpression in cisplatininduced tubular injury, since oxygen radicals are generated in the MIOX-initiated glucuronate/xylulose pathway (19). MIOX, a proximal tubular-specific enzyme, exacerbates kidney redox injury in multiple pathological states (33).…”
Section: Methodsmentioning
confidence: 99%
“…The ARPE19 cell line recapitulates structural, morphological and functional features of RPE cells [62] and was used to design an in vitro model of oxidative stress. As ARPE19 cells with longer culture periods (>1 week) have been reported to be less vulnerable to oxidative stress [63], all experiments were performed two weeks after seeding in 96-well plates with the aim to establish a robust oxidative stress model leading to significant cell damage and cell death [64,65].…”
Section: Establishment Of An In Vitro Oxidative Stress Model Using Exmentioning
confidence: 99%
“…Studies showed that a low dose of sodium iodate significantly decreased phagocytotic activity, cellular acidity, and autophagy, leading to RPE cell degeneration [ 54 , 55 ], while a high dosage of sodium iodate increased the expression of pentraxin 3, thereby accelerating RPE cell death [ 56 ]. Another in vitro model was the application of tert -butyl hydroperoxide on human fetal RPE and APRE-19 cells [ 57 ]. Moreover, a hydrogen peroxide-induced AMD cellular model has also been used to test the therapeutic efficacy of piceatannol [ 58 ], scutellarin [ 59 ], and berberine [ 60 ].…”
Section: Disease Mechanisms Of Amdmentioning
confidence: 99%
“…Programmed cell death (PCD) plays an important role in response to stress and the regulation of homeostasis and diseases. Apart from the classical apoptosis, recent basic science studies also discovered novel PCD such as pyroptosis [ 53 ], necroptosis [ 88 ] and ferroptosis [ 57 ], which may contribute to the RPE cell death in AMD ( Figure 2 ). A comparison of the three novel programmed cell deaths has been listed in Table 1 .…”
Section: Overview Of Novel Programmed Cell Death (Pcd)mentioning
confidence: 99%